Peter Longhurst interviewed by Diana Ritch - Longhurst, Peter; Ritch, Diana, 1943- (1983)
Peter Longhurst, a wildlife artist, describes beginning drawing whilst in the Navy; taking up hobby painting in hospital in Australia; being attracted to the colourful Australian birds and flowers; selling his designs to a greeting card company; designing calendars and another card series for John Sands; Hamlyn publishing, limited edition volumes of his hibiscus paintings; his book of camellia paintings; dinner placemat designs for Jason Products; designing advertisements; limited edition prints for artshows; sometimes compromising to meet publishing deadlines; wanting to paint colour; technique; building up shading and colour; using photographs to paint birds and fish; depicting movement; finding specimens for his flower pictures on long walks around Sydney; method for drawing flowers; aim to produce a definitive edition of world hibiscus species; solitary life of the artist.
Also available online
Peter Longhurst was born in the United Kingdom in December 1922, served with the Royal Navy from 1938-1952, migrated to Australia in 1968 and took up painting in the following year.
Transcript available (typescript, 13 leaves)
Timed summary (2 p.).
Keywords: Longhurst, Peter -- Interviews; Wildlife artists -- Australia -- Interviews; Wildlife art -- Australia; Flowers in art -- Australia